Text, Voice-notes, and Emojis: Exploring the use of WhatsApp as a responsive research method for qualitative studies - Mwanda, Ziyanda (Critical Studies in Teaching and Learning, 2023)
Unprecedented times are upon us and the need for ethically responsive online research methods is increasing exponentially. Currently, literature is showing that previously frowned upon methods such as the use of social media continue to offer solutions to traditional research challenges in times of COVID-19 and beyond. This paper describes how the features of WhatsApp were used to respond to the needs of geographically dispersed, working study participants. Tronto’s Ethics of Care framework is employed as a lens to place emphasis on the elements of care this emerging method offers. Participants and the researcher reflected on the high level of responsiveness WhatsApp offered as a method and the drawbacks are also discussed. In conclusion, this paper offers a list of recommendations that researchers need to take into account when using WhatsApp as a method in a context-sensitive manner.